2019
DOI: 10.3390/diseases7010005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Wellbeing, and Symptoms of Dysmenorrhea among University Nursing Students in Greece

Abstract: Dysmenorrhea (pain during menstruation) is one of the most common medical conditions among women of reproductive age. Dysmenorrhea has been studied around the world but not yet in Greece. The aim of the present study was to investigate the prevalence, characteristics, and impact of dysmenorrhea on the wellbeing (exercising, and social and academic functioning) among nursing students in Greece. A cross-sectional study of 637 nursing students was conducted by administering a questionnaire at a university in Athe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
70
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 41 publications
4
70
3
1
Order By: Relevance
“…However, this is lower than the prevalence reported in the Spanish region of Ciudad Real (74.8%), the only study on this subject conducted among Spanish university students [ 19 ]. Compared to European studies, the prevalence was lower than a study carried out on Greek nursing students which identified 89.2% of young people with dysmenorrhea [ 28 ] and lower than a prevalence of 89% identified in young Swedes [ 29 ], although similar to the 62.8% identified in Portuguese women [ 30 ]. These differences among European countries may be related to differences affecting the climate, lifestyle and diet.…”
Section: Discussioncontrasting
confidence: 50%
“…However, this is lower than the prevalence reported in the Spanish region of Ciudad Real (74.8%), the only study on this subject conducted among Spanish university students [ 19 ]. Compared to European studies, the prevalence was lower than a study carried out on Greek nursing students which identified 89.2% of young people with dysmenorrhea [ 28 ] and lower than a prevalence of 89% identified in young Swedes [ 29 ], although similar to the 62.8% identified in Portuguese women [ 30 ]. These differences among European countries may be related to differences affecting the climate, lifestyle and diet.…”
Section: Discussioncontrasting
confidence: 50%
“… 2 , 3 , 13 It is well known that increased psychological stress is a predisposing factor for developing dysmenorrhea; therefore, the stressful lifestyle of medical students could explain the high prevalence of dysmenorrhea in our studied population. 14 , 15 Moreover, in another Nepalese study, up to 85% of students experienced an increase in the frequency and severity of dysmenorrhea after enrolling in medical school. 16 However, some studies have reported prevalence as high as 94% and others, as low as 53% or 43%.…”
Section: Discussionmentioning
confidence: 99%
“…This condition can occur without any pathological pelvic disease (primary dysmenorrhea) or borne of a pelvic disease (secondary dysmenorrhea) usually in women above 20 years of age. 1 2 Symptoms associated with dysmenorrhea include diarrhoea, headache, nausea, and vomiting. 3 Various studies have reported varying dysmenorrhea prevalence across varying ages and ethnicities.…”
Section: Introductionmentioning
confidence: 99%